2009
DOI: 10.1021/es902582y
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Contaminant Burdens in an Arctic Fish, Burbot (Lota lota), in a Warming Climate

Abstract: The temporal patterns of mercury (Hg), polychlorinated biphenyls (PCBs), and other contaminants in Arctic aquatic biota are usually attributed to changing atmospheric sources. However, climate variability and change is another means of altering contaminant fate and bioavailability. We show here that the concentrations of Hg and PCBs in Mackenzie River burbot ( Lota lota ), a top predator fish and important staple food for northern Canadian communities, have increased significantly over the last 25 years despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
146
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(155 citation statements)
references
References 35 publications
9
146
0
Order By: Relevance
“…In studies of four lakes in the Canadian Arctic Archipelago and the Yukon, sediment fluxes of THg increased during the 20th century and were correlated with an increase in aquatic productivity inferred by diatom abundances and chemical characterisation of the sedimented organic matter. [62,65,66] Similarly, the amount of organic matter is an important factor explaining the spatial distribution of Hg in sediments within and among Arctic lakes. Organic matter, which strongly binds Hg, [67] occurs at low concentrations in nearshore and deep-water sediments of High Arctic lakes (typically less than 10 % dry weight (DW), total organic carbon).…”
Section: Since 1993 Prof Henrik Skov Has Worked As Principal Scientimentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of four lakes in the Canadian Arctic Archipelago and the Yukon, sediment fluxes of THg increased during the 20th century and were correlated with an increase in aquatic productivity inferred by diatom abundances and chemical characterisation of the sedimented organic matter. [62,65,66] Similarly, the amount of organic matter is an important factor explaining the spatial distribution of Hg in sediments within and among Arctic lakes. Organic matter, which strongly binds Hg, [67] occurs at low concentrations in nearshore and deep-water sediments of High Arctic lakes (typically less than 10 % dry weight (DW), total organic carbon).…”
Section: Since 1993 Prof Henrik Skov Has Worked As Principal Scientimentioning
confidence: 99%
“…[131] The implication that fresh algal organic matter provides an important Hg complexation mechanism in Arctic freshwater is further supported by the strong association between historical fluxes and concentrations of Hg and algal organic carbon in sediment cores from several Arctic lakes. [62,65,66] Transfer pathways for mercury into Arctic food webs In temperate environments, inorganic Hg is methylated predominantly by microbes. From a combination of laboratory and field studies it is believed that there are two main inorganic Hg uptake pathways by microbes that lead to Hg methylation.…”
Section: Bioavailability Of Mercurymentioning
confidence: 99%
“…Several studies have shown that climate warming plays a significant role in algal productivity by using the S2 proxy in the Arctic lakes during recent decades (Outridge et al, 2005(Outridge et al, , 2007Stern et al, 2009;Carrie et al, 2010). However, Kirk et al (2011) investigated 14 Canadian Arctic and subArctic lakes and found that the relationship between the S2 proxy and climate warming was irrelevant.…”
Section: Introductionmentioning
confidence: 99%
“…Algal organic matter (AOM) as a biological pump effect in Arctic and sub-Arctic lakes may significantly affect the concentrations of mercury in sediments during the past decades (Sanei and Goodarzi, 2006;Outridge et al, 2007;Carrie et al, 2009;Stern et al, 2009). …”
Section: Introductionmentioning
confidence: 99%